2015
DOI: 10.1021/acssuschemeng.5b00749
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced and Ultraviolet Resistant Silks from Silkworms Fed with Titanium Dioxide Nanoparticles

Abstract: As the perfect combination of strength and luster, silkworm silks have been widely used in many fields but still need improvements. This paper demonstrates an in vivo uptake of titanium dioxide (TiO 2 ) nanoparticles by silkworms, leading to the direct production of intrinsically modified silk. The nanoparticles can be easily incorporated into the silk gland of silkworm by using this method due to the interactions between TiO 2 and silk fibroin molecules. Infrared spectra indicate that TiO 2 nanoparticles conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 45 publications
8
89
0
Order By: Relevance
“…Researchers [24] also reported the largest agglomeration of silk fibroin compounds with the highest concentration of Ca, and it was shown that the fibroin macromolecular chains form complex with Cu ions, leading to more crystalline beta-type (beta-sheets) planes on the structure of silk fiber thread [13]. Similar results were reported using TiO 2 nanoparticles [15]. High additive amount is likely to exceed the absorbing capacity of the silkworms, and the agglomeration of nanoparticles at a high concentration may make the interaction between the metals and the silk fibroin difficult.…”
Section: X-ray Diffractionmentioning
confidence: 57%
See 2 more Smart Citations
“…Researchers [24] also reported the largest agglomeration of silk fibroin compounds with the highest concentration of Ca, and it was shown that the fibroin macromolecular chains form complex with Cu ions, leading to more crystalline beta-type (beta-sheets) planes on the structure of silk fiber thread [13]. Similar results were reported using TiO 2 nanoparticles [15]. High additive amount is likely to exceed the absorbing capacity of the silkworms, and the agglomeration of nanoparticles at a high concentration may make the interaction between the metals and the silk fibroin difficult.…”
Section: X-ray Diffractionmentioning
confidence: 57%
“…High additive amount is likely to exceed the absorbing capacity of the silkworms, and the agglomeration of nanoparticles at a high concentration may make the interaction between the metals and the silk fibroin difficult. According to these authors [15], TiO 2 nanoparticles interacted with the protein molecules and restricted the movement of protein molecules during secretion, then it was difficult to increase the nucleation sites of crystallization for silk fibroin around TiO 2 nanoparticles. Figure 5 X-ray diffractograms of silk fiber thread produced in different conditions.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the TiO 2 were incorporated into silk fibers, the breaking strength and elongation of TiO 2 modified silk fiber can be enhanced to 548 ± 33 MPa and 16.7 ± 0.8%, respectively. Moreover, the TiO 2 functionalized silk fibers display well Anti UV properties compared with neat silk fibers …”
Section: Functionalization Of Silk Via Mesoscopic Materials Assemblymentioning
confidence: 99%
“…Previously many attempts have been made to increase the silk production by feeding the larvae with compounds like royal jelly, cowpea,, and Juvenile hormone analog, methoprene . In vivo uptake of titanium dioxide nano particles by silkworms lead to increase in the mechanical properties of silk fibroin . Dietary supplementation with threonine and valine showed effect on mechanical properties .…”
Section: Introductionmentioning
confidence: 99%